School‐Based Programs Aimed at the Prevention and Treatment of Obesity: Evidence‐Based Interventions for Youth in Latin America2. (23rd July 2013) - Lobelo, Felipe; Garcia de Quevedo, Isabel; Holub, Christina K.; Nagle, Brian J.; Arredondo, Elva M.; Barquera, Simón; Elder, John P.
ABSTRACT: BACKGROUND: Rapidly rising childhood obesity rates constitute a public health priority in Latin America which makes it imperative to develop evidence‐based strategies. Schools are a promising setting but to date it is unclear how many school‐based obesity interventions have been documented in Latin America and what level of evidence can be gathered from such interventions. METHODS: We performed a systematic review of papers published between 1965 and December 2010. Interventions were considered eligible if they had a school‐based component, were done in Latin America, evaluated an obesity related outcome (body mass index [BMI], weight, %body fat, waist circumference, BMI z ‐score), and compared youth exposed vs not exposed. RESULTS: Ten studies were identified as having a school‐based component. Most interventions had a sample of normal and overweight children. The most successful interventions focused on prevention rather than treatment, had longer follow‐ups, a multidisciplinary team, and fewer limitations in execution. Three prevention and 2 treatment interventions found sufficient improvements in obesity‐related outcomes. CONCLUSIONS: We found sufficient evidence to recommend school‐based interventions to prevent obesity among youth in Latin America. Evidence‐based interventions in the school setting should be promoted as an important component for integrated programs, policies, and monitoring frameworks designed to reverse the childhood obesity in the region.